PREPARING OF DEMOCRATIC EDUCATION LEADERS IN ISLAMIC EDUCATIONAL LEADERSHIP PERSPECTIVE - Mawardi Lubis (Universitas Islam Negeri Fatmawati Sukarno, 2017)
The objective of this research was to understand preparing of democratic education leaders in Islamic educa- tion leadership perspective. The approach be used in research was library research with a kind of qualitative research. The prosess of gathering data/information was used review method/technique through references review and includ- ing social media those connect to preparing democratic education leaders in Islamic education leadership perspective and the analytic technique was descriptive analytic technique. The research result indicates that preparing democratic education leaders in Islamic education leadership perspective had to be done the real actions for students, for every component of educational actvity had to be connected to theoretic and practice Islamic democratic leadership aspect. Keywords: leader, education, democratic, leadership, Islamic